Indirubin Derivative 7-Bromoindirubin-3-Oxime (7Bio) Attenuates Aβ Oligomer-Induced Cognitive Impairments in Mice - Chen, Liping; Huang, Chunhui; Shentu, Jieyi; Wang, Minjun; Yan, Sicheng; Zhou, Fei; Zhang, Zaijun; Wang, Chuang; Han, Yifan; Wang, Qinwen; Cui, Wei (Frontiers in Molecular Neuroscience, 2017)
Indirubins are natural occurring alkaloids extracted from indigo dye-containing plants. Indirubins could inhibit various kinases, and might be used to treat chronic myelocytic leukemia, cancer and neurodegenerative disorders. 7-bromoindirubin-3-oxime (7Bio), an indirubin derivative derived from indirubin-3-oxime, possesses inhibitory effects against cyclin-dependent kinase-5 (CDK5) and glycogen synthase kinase-3β (GSK3β), two pharmacological targets of Alzheimer’s disease (AD). In this study, we have discovered that 2.3-23.3 μg/kg/kg 7Bio effectively prevented β-amyloid (Aβ) oligomer-induced impairments of spatial cognition and recognition without affecting bodyweight and motor functions in mice. Moreover, 7Bio potently inhibited Aβ oligomer-induced expression of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Furthermore, 7Bio significantly prevented the decreased expression of synapsin-1 and PSD-95, biomarkers of pre-synaptic and post-synaptic proteins in Aβ oligomer-treated mice. The mean optical density (OD) with hyper-phosphorylated tau (pTau), glial fibrillary acidic protein (GFAP)and CD45 positive staining in the hippocampus of 7Bio-treated mice were significantly decreased compared to those of Aβ oligomer-treated mice. In addition, Western blotting analysis showed that 7Bio attenuated Aβ oligomer-decreased expression of pSer9-GSK3β. Those results suggested that 7Bio could potently inhibit Aβ oligomer-induced neuroinflammation, synaptic impairments, tau hyper-phosphorylation, and activation of astrocytes and microglia, which may contribute to the neuroprotective effects of 7Bio. Based on these findings, we expected that 7Bio might be developed as a novel anti-AD lead compound.